ParticipACTION: A mass media campaign targeting parents of inactive children; knowledge, saliency, and trialing behaviours - Gauvin Lise; Bauman Adrian; Craig Cora L; Robertson Jennifer; Murumets Kelly (BMC, 2009)
Abstract Background In late 2007, Canada's ParticipACTION national physical activity mass media campaign was re-launched, with an initial campaign targeting parents of elementary school-aged children. The campaign informed them about the risks of physical inactivity for children and youth. The purpose of this study was to assess campaign awareness and understanding following the campaign, and to identify whether exposure to this campaign was likely associated with behaviour change. Methods A convenience sample of 1,500 adults was recruited though an existing panel (n = 60,000) of Canadian adults to participate in online surveys. Initial campaign exposure included "prompted" and "unprompted" recall of specific physical activity messages from the 2007 ParticipACTION campaign, knowledge of the benefits of PA, saliency, and initial trial behaviours to help their children become more active. Results One quarter of respondents showed unprompted recall of specific message content from the ParticipACTION campaign, and prompted recall was 57%. Message recall and understanding was associated with knowledge about physical activity, and that in turn was related to high saliency. Saliency was associated with each of the physical activity-related trial behaviours asked. Conclusion Campaign awareness and understanding was high following this ParticipACTION campaign, and was associated with intermediate campaign outcomes, including saliency and trial behaviours. This is relevant to campaign evaluations, as it suggests that an initial focus on influencing awareness and understanding is likely to lead to more substantial change in campaign endpoints.